Application of Gliricidia sepium Tree Leaves and Nitrogen Fertilizer to Improve Tomato Production and Soil Properties (Annals of Bangladesh Agriculture, 2021)
Excess use of agrochemicals for intensive cultivation affects crop quality and destroys agro-ecosystems, and eventually creates health hazards. The study aims to investigate the effect of Gliricidia sepium (GS) tree leaf as suitable green manures for supplementing nutrient supply along with nitrogen (N) fertilizer to produce quality tomato and soil fertility improvement. A field experiment was conducted at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh, from November 2016 to March 2017. The experiment was laid out in a randomized complete block design (two factors) with three replications. There were nine treatment combinations with three levels of GS tree leaves (5, 10 and 15 t ha−1) and three doses of N (0, 50 and 100% of the recommended dose of fertilizer). The highest tomato yield was recorded in GS15×N100 treatment combination, which was 41.68% higher compared to the control treatment. Decreasing C: N ratio in increasing dose of GS and N treated plot indicated the quality of tree leaves that ensures faster decomposition and high nutrient release pattern of this species. Increasing rate of soil pH and cation exchange capacity (CEC) in different treatments as compared to initial soil showed soil fertility improvement. Overall, the results indicated that quality tomato could be grown successfully by the application of G. sepium tree leaves along with an appropriate amount of N fertilizer.Ann. Bangladesh Agric. (2020) 24(1) : 77-87